Pastryfeel Sdn Bhd / Aziahanim Azah … [et al.] - AZAH, AZIAHANIM; SAMAT, SALBIAH; MALEK IBRAHIM, NUR MURSHIDA; DEMAN, NOORHAIRANI; RIDZWAN, NUR AMIERA MUDRYQAH (2019)
Specifically, we would like to give our acknowledgement to the owner of Pastryfeel Miss Raja Mariah Jameelah Raja Badri Shah who are very cooperate in addressing each of our questions throughout the talk. We appreciate her time and permission to make her shop as ourcase study model A Indeed these case study is a collaboration of diverse mind with source. To all contributors that are all of our group member Aziahanim Azah, Salbiah Samat, Nur Murshida Malek Ibrahim, Nur Amiera Mudryqah Ridzwan and Noorhairani Deman. With all of their hard work we are able to finish the case study on time.